Automated equipment management & maintenance system (AEMS) - Quek, Teng Yeow (2015)
Servicing of commercial refrigeration equipment is prevalent throughout the F&B industry in Singapore as food equipment inevitably breaks down with constant use. Currently, each service job is manually scheduled and communicated to each stakeholders involved, between the F&B Owners and the service provider. With each increasing store, managing of these service jobs can be a tedious and time-consuming process. In this project, an equipment management system is proposed to assist both parties manage the status of their equipment more efficiently.In order to develop a robust and user-friendly equipment management system, some research has been done on similar systems available in the market. The strengths and weakness obtained from the research were noted and taken into consideration in the design of the system. Moreover, with the complexity of web application and hardware integration, research has been done on various technologies available that can be used in the system. With the knowledge and objective in mind, the Automated Equipment Management & Maintenance System is designed with remote monitoring capabilities such as automatic alerting, catered for all users in the servicing process. It can further consolidate past service activities and compute the cost of servicing, allowing for better decision-making. To enhance its functionality, the report generation and scheduling modules are added to facilitate service planning. Although the functional requirements were met, additional features could be added to extend the capabilities of the system. Recommendations include having a mobile view, enhanced hardware and the migration towards a cloud server for better scalability and security.